Association Between Severe Periodontitis and Cognitive Decline in Older Adults - Yash Brahmbhatt; Hend Alqaderi; Zahra Chinipardaz (Life)
(1) Background: Periodontal disease, a progressive inflammatory condition, disrupts the oral microbiome and releases inflammatory cytokines, leading to systemic issues, including cognitive decline. This study investigates the association between severe periodontitis and cognitive decline, exploring the role of alkaline phosphatase (ALP), an enzyme linked to systemic inflammation, as an effect modifier. (2) Methods: We analyzed cross-sectional data from the 2013–2014 National Health and Nutrition Examination Survey (NHANES). Severe periodontitis was defined using the Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics (AAP) case definition. A weighted multivariable logistic regression model assessed the association between severe periodontitis and cognitive decline. An interaction term examined ALP’s role as an effect modifier. (3) Results: This study included 1265 participants aged 65 and older. After adjusting for confounders, each one-point increase in cognitive function score was associated with a 2% decrease in the odds of severe periodontitis (OR = 0.98; 95% CI = 0.97–0.99; p = 0.008). ALP was a significant effect modifier in the relationship between severe periodontitis and cognitive decline. (4) Conclusions: This study, using a representative U.S. adult population aged 65 and over, suggests that lower cognitive performance correlates with higher likelihood of severe periodontitis. ALP enhances the association between severe periodontitis and cognitive decline.